Maillard Reaction in Flour Product Processing: Mechanism, Impact on Quality, and Mitigation Strategies of Harmful Products - Yajing Qi; Wenjun Wang; Tianxiang Yang; Wangmin Ding; Bin Xu (Foods)
The Maillard reaction refers to the reaction between carbonyl compounds with reducing properties and amino-containing compounds that undergo condensation and polymerization to produce melanoidins. In flour product processing, the Maillard reaction is a critical chemical reaction influencing color, flavor, nutrition, and safety. A moderate Maillard reaction contributes to desirable color and flavor profiles in flour products, whereas an excessive reaction leads to amino acid loss and the formation of harmful substances, posing potential health risks. This review summarizes the substrate sources, reaction stages, influencing factors, impact on quality, and mitigation strategies of harmful products, aiming to provide a reference for regulating the Maillard reaction in flour product processing. Currently, most existing mitigation strategies focus on inhibiting harmful products, while research on the synergistic optimization of color and flavor remains insufficient. Future research should focus on elucidating the molecular mechanisms of reaction pathways, understanding multi-factor synergistic effects, and developing composite regulation technologies to balance the sensory quality and safety of flour products.